2020
DOI: 10.7717/peerj.8426
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptome analysis of alfalfa reveals six key biological processes of senescent leaves

Abstract: Leaf senescence is a complex organized developmental stage limiting the yield of crop plants, and alfalfa is an important forage crop worldwide. However, our understanding of the molecular mechanism of leaf senescence and its influence on biomass in alfalfa is still limited. In this study, RNA sequencing was utilized to identify differentially expressed genes (DEGs) in young, mature, and senescent leaves, and the functions of key genes related to leaf senescence. A total of 163,511 transcripts and 77,901 unige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…We found 1,570 stem-speci c genes, among which those signi cantly enriched in the phenylpropanoid biosynthesis pathway might affect the feed value of B. catharticus, as phenylpropanoid metabolism is a major pathway of lignocellulose biosynthesis [7,25]. While we identi ed 3,030 leaf-speci c genes mainly related to the photosynthetic pathways, which might be of bene t in the improvement of leaf photosynthetic e ciency and biomass parameters, analysis of leaf transcriptome of alfalfa identi ed 5,133 DEGs and senescenceassociated pathways, including ribosome and phenylpropanoid biosynthesis, and starch and sucrose metabolism pathways, and suggested a novel interpretation of the molecular mechanisms of leaf senescence [26]. In addition, our comparative analysis showed that the ribosome pathway was the most signi cantly enriched pathway among 1,803 seed-speci c genes.…”
Section: Tissue-speci C Gene Expressionmentioning
confidence: 83%
“…We found 1,570 stem-speci c genes, among which those signi cantly enriched in the phenylpropanoid biosynthesis pathway might affect the feed value of B. catharticus, as phenylpropanoid metabolism is a major pathway of lignocellulose biosynthesis [7,25]. While we identi ed 3,030 leaf-speci c genes mainly related to the photosynthetic pathways, which might be of bene t in the improvement of leaf photosynthetic e ciency and biomass parameters, analysis of leaf transcriptome of alfalfa identi ed 5,133 DEGs and senescenceassociated pathways, including ribosome and phenylpropanoid biosynthesis, and starch and sucrose metabolism pathways, and suggested a novel interpretation of the molecular mechanisms of leaf senescence [26]. In addition, our comparative analysis showed that the ribosome pathway was the most signi cantly enriched pathway among 1,803 seed-speci c genes.…”
Section: Tissue-speci C Gene Expressionmentioning
confidence: 83%
“…While we identified 3,030 leaf-specific genes mainly related to the photosynthetic pathways, which might be of benefit in the improvement of leaf photosynthetic efficiency and biomass parameters. Analysis of leaf transcriptome of alfalfa identified 5,133 DEGs and senescence-associated pathways, including ribosome and phenylpropanoid biosynthesis, and starch and sucrose metabolism pathways, and suggested a novel interpretation of the molecular mechanisms of leaf senescence [ 26 ]. In addition, our comparative analysis showed that the ribosome pathway was the most significantly enriched pathway among 1,803 seed-specific genes.…”
Section: Discussionmentioning
confidence: 99%
“…1 ) [ 35 , 44 , 53 ]. Other basic metabolic changes that regulate senescence were reported in young and mature but not yet senescing leaves of both perennial and annual plants: for instance, downregulation of genes that are involved in amino acid biosynthesis and a decrease in the level of amino acids in developing Medicago sativa (alfalfa) and Arabidopsis leaves [ 6 , 35 , 54 ]. Likewise, in a recent study, age-related differences were observed in metabolites of leaves collected from perennial tea crop Camellia sinensis plants aged 8 and 25 years old [ 55 ].…”
Section: Systems Biology Approaches Of Ageing Suggest Primary Metabolic Processes As Major Age-regulating Factorsmentioning
confidence: 99%